Jump to content
New Registrations Suspended Read more... ×
Estatia

Can you figure it out?c For the prize?

Recommended Posts

Now that you figured this part out the next part is a math problem solve it and you get 10 points! Give me the answer with this color code(hex) #202020 so no one else can understand..

Here is the problem (x-4)(x+9)   

Edited by Estatia

Share this post


Link to post
Share on other sites

SHITE! I Tried but hey, I suck at math anyway. xD

Edited by Oakmi

Share this post


Link to post
Share on other sites
3 hours ago, Oakmi said:

(x-4)(x+9) = 0

Sorry incorrect

Share this post


Link to post
Share on other sites

=(x + -4)(x + 9) = 0

= (-4 + x)(x + 9) = 0

= (-4 + x)(9 + x) = 0

= (-4 + x) * (9 + x) (-4(9 + x) + x(9 + x)) = 0 ((9 * -4 + x * -4) + x(9 + x)) = 0 ((-36 + -4x) + x(9 + x)) = 0 (-36 + -4x + (9 * x + x * x)) = 0 (-36 + -4x + (9x + x2)) = 0

= -4x + 9x = 5x (-36 + 5x + x2) = 0

=-36 + 5x + x2 = 0

=(-9 + -1x)(4 + -1x) = 0.

I'm no good in math BTW.

Edited by AniMeFReaK

Share this post


Link to post
Share on other sites

7x-36 

Its been a while but I'm pretty sure that this is correct.

Edited by Baku

Share this post


Link to post
Share on other sites
On 2018/2/13 at 12:41 AM, Estatia said:

Now that you figured this part out the next part is a math problem solve it and you get 10 points! Give me the answer with this color code(hex) #202020 so no one else can understand..

Here is the problem (x-4)(x+9)   

How do you even solve that? It is an expression there is no answer to it. If you had set it equal to something or y then it would be possible. But assuming you wanted it set equal to 0 the answers are 4,-9

Edited by Whutever42

Share this post


Link to post
Share on other sites
22 hours ago, Oakmi said:

(x-4)(x+9) = 0

 

18 hours ago, Estatia said:

Sorry incorrect

 

8 hours ago, AniMeFReaK said:

=(x + -4)(x + 9) = 0

= (-4 + x)(x + 9) = 0

= (-4 + x)(9 + x) = 0

= (-4 + x) * (9 + x) (-4(9 + x) + x(9 + x)) = 0 ((9 * -4 + x * -4) + x(9 + x)) = 0 ((-36 + -4x) + x(9 + x)) = 0 (-36 + -4x + (9 * x + x * x)) = 0 (-36 + -4x + (9x + x2)) = 0

= -4x + 9x = 5x (-36 + 5x + x2) = 0

=-36 + 5x + x2 = 0

=(-9 + -1x)(4 + -1x) = 0.

I'm no good in math BTW.

 

5 hours ago, Baku said:

7x-36 

Its been a while but I'm pretty sure that this is correct.

 

4 hours ago, Whutever42 said:

How do you even solve that? It is an expression there is no answer to it. If you had set it equal to something or y then it would be possible. But assuming you wanted it set equal to 0 the answers are 4,-9

I'm sorry I should have clarified the solution a problem like this has two answers the ones are: x^2(this is x squared)

X^2+5x-36, x=4 x=-9

I will make that is more clear: Find the x and y intercept(s) with the equation y=x^2+17+72

Share this post


Link to post
Share on other sites
15 hours ago, Estatia said:

 

I will make that is more clear: Find the x and y intercept(s) with the equation y=x^2+17+72

The x intercepts are -9 and -8 and the y intercept is 72

Share this post


Link to post
Share on other sites

Please sign in to comment

You will be able to leave a comment after signing in



Sign In Now

Anime Forums is where fans from around the world can gather to discuss anime and Japanese culture!  All anime fans are welcome. Take a moment to join us now!
×